Comparison of Three Prosthodontic Treatment Modalities for Patients with Periodontally Compromised Anterior Mandibular Teeth: A 2-year follow-up study - Asja Čelebić; Sanja Peršić; Ines Kovačić; Dino Buković; Nikolina Lešić; Ksenija Rener-Sitar (University of Zagreb. School of Dental Medicine, 2019)
Objectives: To prospectively assess self-perceived chewing function (CF) and oral health-related quality of life (OHRQoL) in geriatric patients after receiving three different treatment modalities in the mandible: removable partial denture (CD-RPD), complete denture (CDs), or complete overdenture supported by mini dental implants (CD-MDI). At baseline, all patients had mobile anterior teeth (1 mm or >) and missing posterior teeth in the mandible. Patients were completely edentulous in the maxilla. After treatment, patients were recalled at the 3-month and the 2-year post-treatment period. Materials and Methods: A total of 176 patients participated (CD group, n=68; CD-RPD group, n=58; CDMDI group, n=50). Self-reported CF was assessed using the Chewing Function questionnaire (CFQ), The OHRQoL was evaluated using the OHIP14 questionnaire, which the patients completed 1. before treatment, 2. three months after treatment, and 3. at the 2-year post-treatment stage. Results: The OHRQoL and the self-perceived CF significantly improved in all groups after treatment (p<0.01). The highest improvement of a CF was recorded in the CD-MDI group. The OHRQoL was significantly higher in the CD-MDI group in comparison to the CDs group after treatment (p<0.01). At the 2-year post-treatment stage, self-perceived CF significantly further improved in the CD-MDI group, while it worsened in the CD and the CD-RPD groups (p<0.01). The same pattern was recorded for the OHIP14 summary scores. The highest amount of denture repairs and adjustments was recorded in the CDRPD group, although maintenance was also demanding in the CD-MDI group. Conclusion: Within the limitations of this study, rehabilitation with mandibular MDI retained overdenture can be considered as preferred treatment with the constant improvement of OHRQoL and a chewing function in comparison to mandibular CD or mandibular RPD option in patients with mobile anterior mandibular teeth.